GNC University: A Case Study in Partnering Business and Education through Distance Learning - Lisa K. Lundy; Tracy A. Irani; R. Elaine Turner; Susan S. Percival; Britton McPherson (Journal of Applied Communications, 2004)
In 2002, General Nutrition Corporation, Inc. contacted the Department of Food Science and Human Nutrition at the University of Florida to collaborate in offering a series of courses in introductory nutrition for GNC employees in order to equip them with basic nutrition knowledge. The purpose of this case study was to describe the GNC University program as a model for business-education partnerships via distance education, to describe student expectations for the GNC University experience, to describe student reactions to the GNC University experience, and to describe the reaction of teaching assistants to their experience with GNC University. There were several key findings in this study. Students’ expectations are to increase in nutrition knowledge, professionally and personally, and to increase in their technological skills. There is a need, in future evaluation of this program, to measure whether students feel their expectations of increased knowledge and technological skills are being met. Additionally, focus groups with teaching assistants revealed a need for greater preparation for assisting students with technical difficulties. Overall, this program shows promise for business-education partnerships through distance education.